EVALUATION OF ANTI-DIABETIC ACTIVTY OF DIFFERENT EXTRACTS OF MYRISTICA FRAGRANS HOUTT: IN VITRO AND IN SILICO STUDIES - Sivaraj, Saranya; Kannayiram, Gomathi; Dasararaju, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study is aimed to evaluate the anti-diabetic effect of sequentially extracted (hexane, dichloromethane, ethyl acetate, and ethanol) Myristica fragrans houtt (mace) through in vitro and in silico studies. Methods: The in vitro anti-diabetic effect of the sequentially extracted plant were evaluated for its alpha-amylase inhibitory activity and the potential binding was studied by in silico studies using Schrödinger Maestro. Results: All extracts showed dose dependent alpha-amylase inhibitory effect. At concentration 500 µg/ml, all the extracts showed more than 60% inhibition of the alpha-amylase enzyme and the highest inhibition (81.30%) at 500 µg/ml was observed in DCM extract of mace. Potential compounds were identified by in silico molecular docking studies of alpha-amylase with phytocomponents from DCM extract. Among the top three compounds from virtual screening, induced fit docking studies revealed 2,5-bis(3,4-dimethoxyphenyl)-3,4-dimethyloxolane possessed better binding affinity when compared with the drug metformin. Conclusion: The obtained in vitro and in silico results suggest that all extracts of Myristica fragrans can be used successfully for the management of diabetes mellitus. Keywords: Myristica fragrans, Mace, Sequential extraction, Alpha-amylase, Molecular docking.